Technical Note: New Z-BREAKSS: Post-tensioned Rocking Connection Detail Free of Beam Growth - Dowden, Daniel M.; Bruneau, Michel (Engineering Journal, 2011)
This technical note concisely presents the details of a post-tensioned rocking moment connection (PT-RMC) concept that could be implemented in steel plate shear wall (SPSW) and moment-resisting frame (MRF) systems, along with preliminary results from limited SAP2000 cyclic nonlinear static pushover and time-history analyses that verify its anticipated behavior. The partial research results presented here could be of benefit in ongoing discussions about practical implementation and design codification of PT-RMCs [aka post-tensioned energy dissipating (PTED) or self-centering moment-resisting (SC-MRF) connections].